METHODS OF LEARNING TO RECOGNIZE THE QURAN AT ULUMUL QUR'AN MIDDLE SCHOOL PIDIE JAYA - Afriani, Afriani; Dhiauddin, Dhiauddin; Ismail, Nazaruddin (MSJ : Majority Science Journal, 2025)
This study explores the significance of Qur'anic memorization (tahfidzul Qur'an) in developing both academic and character aspects of students at SMP Ulumul Qur'an Pidie Jaya. Employing a qualitative approach, data were gathered through observation, interviews, and document analysis. The findings indicate that the tahfidz program is conducted within a religious boarding environment, integrated with both formal and religious curricula, and emphasizes intensive repetition (taqrir), simaan, muraja'ah, and halaqah. Supporting factors include a conducive environment, teacher support, adequate facilities, and religious motivation. The main constraints involve limited time due to a demanding academic schedule and low student motivation when driven solely by parental pressure. Consequently, the flexibility of memorization methods tailored to students' characteristics, supported by intensive collaboration between the school and the boarding facility, serves as the key to the successful implementation of the Qur'anic memorization program at SMP Ulumul Qur'an Pidie Jaya.